DAMAGE POTENTIAL OF EARTHQUAKE GROUND MOTIONS RECORDED IN SOUTHERN CENTRAL AMERICA - Santana Barboza, Guillermo; Terán Gilmore, Amador (Universidad de Costa Rica, 2013)
A total of 18 different components of earthquake ground motion recorded in Central America were selected to conductan evaluation oftheir damage potential. Emphasis was placed in ground motions recorded during recent seismic activity inCosta Rica. For the purpose of comparison, five records obtained in different parts ofthe world were included in the study. Asa mean ofidentif)'ing the damage potential ofthe records, the input energy as well as the plastic hysteretic energy speCtra werecalculated for different levels of displacement ductility and a viscous damping coefficient ~=0.05. The effect of duration ofground motion was studied by introducing the non dimensional parametery and the target ductility μTAR. The parameteryis a function of the maximum displacement and the plastic hysteretic energy dissipation demands. The calculations wereperformed for single-degree-of-freedom systems with an elastoplastic hysteretic behavior. Other response quantities consideredwere the constant strength ductility demands and constant ductility strength demands. The results are contrasted withthe current seismic design recommendations for the region as presented in the latest building codes available.